The Profile of Immunophenotype and Genotype Aberrations in Subsets of Pediatric T-Cell Acute Lymphoblastic Leukemia - Noronha, Elda Pereira; Marques, Luísa Vieira Codeço; Andrade, Francianne Gomes; Thuler, Luiz Claudio Santos; Terra-Granado, Eugênia; Pombo-de-Oliveira, Maria S.; , Brazilian Collaborative Study Group of Acute Leukemia; da Paz Zampier, Carolina; da Conceição Barbosa, Thayana; Chagas Neto, Paulo; Dallapicola Brisson, Gisele; dos Santos Bueno, Filipe Vicente; et al. (Frontiers in Oncology, 2019)
T-cell acute lymphoblastic leukemia (T-ALL) is a biologically heterogeneous malignancy, which reflects distinctive stages of T-cell differentiation arrest. We have revisited a cohort of pediatric T-ALL in order to test if immunophenotypes associated with molecular alterations would predict the patient’s outcome. Genetic mutations, translocations and copy number alterations were identified through Sanger sequencing, RT-PCR, FISH and multiplex ligation-dependent probe amplification (MLPA). We defined 6 immunophenotypic T-ALL subtypes through multiparametric flow cytometry: early T-cell precursor (ETP, n=27), immature (n=37), early cortical (n=15), cortical (n=50), late cortical (n=53), CD4/CD8 double negative mature (n=31), double positive mature (n=35) and simple positive mature (n=31) T-ALL. Deletions (del) or amplifications (amp) in at least one gene were observed in 87% of cases. The most frequent gene alterations were CDKN2A/Bdel (71.4%), NOTCH1mut (47.6%) and FBXW7mut (17%). ETP-ALL had frequent FLT3mut (22.2%) and SUZ12del (16.7%) (p<0.001), while CDKN2A/Bdel were rarely found in this subtype (p<0.001). The early cortical T-ALL subtype had high frequencies of NOTCH1mut and IL7Rmut (71%, 28.6%, respectively), whereas, mature T-ALL with double positive CD4/CD8 had the highest frequencies of STIL-TAL1 (36.7%), LEF1del (27.3%) and CASP8AP2del (22.7%). The co-existence of two groups of T-ALL with NOTCH1mut/IL7Rmut, and with TLX3/SUZ12del/NF1del/IL7Rmut were characterized with statistical significance (p<0.05) but, only STIL-TAL1 (pOS 47.5%) and NOTCH1WT/FBXW7WT (pOS 68.4%) are predictors of poor T-ALL outcomes. In conclusion, we have observed that T-ALL with distinctive genomic alterations can be predicted by initial flow cytometry analysis.